Sistem Informasi E-Voting pada Pemilihan Umum Ketua RW dengan Pengujian Black-Box dan Analisis Regresi Variabel Dummy - Abdus Salam; Fauzan Putraga Albahri; Fathurrahmad (KITA Institute, 2022)
The purpose of this study was to develop a model of a student's final project recommendation system by applying the Collaborative Filtering (CF) method. Agile Development Methods (ASD) is used in software development where this method is widely used for software development because it can produce system requirements data that is more descriptive and easy to implement into software. After going through the process of completing this research, the results of this study; 1) In knowing the topic or research theme in the final project, students with an expert system can be seen from the themes and sub-themes and valid calculations are carried out in helping students to find out the research title for the final project quickly, 2) By applying the Collaborative Filtering (CF) method ) in detecting research topics or themes at AMIK Indonesia, it can produce valid calculations that are the same as manual calculations so that the selection process can be carried out quickly and accurately, 3) In designing this application, it consists of the main menu page, a list of research topics, FAQs and about applications with using the programming language PHP, ReachJS and MySQL as data processing in the recommendation of the student's final project, and 4) The test is carried out using Mean Absolute Error (MAE), root-mean-square error (RMSE), Recall Value, and F-Measure. The results of the test evaluation show that the Collaborative Filtering (CF) method is quite accurate with the resulting recommendations.